Strategi Distribusi Pemasaran Guna Meningkatkan Produk Perusahaan: Studi Kasus pada PT. Bintang Sidoraya - Faiz Hanan Fahreza; Ratna Rostika (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This internship report contains matters relating to marketing distribution strategies to improve products at PT. Bintang Sidoraya. This research uses marketing management theory and marketing mix strategies, namely segmenting, targeting and positioning strategies with a 4P marketing mix approach (Place, product, price and promotion). PT. Bintang Sidoraya is a company that operates as a beverage distributor company. Business activities at PT Bintang Sidoraya include purchasing, stock inventory and sales transactions. This research uses a qualitative approach with descriptive methods through interviews and direct observation. The conclusion of this research is that PT Bintang Sidoraya offers their products to a wide market segment and reaches all consumer classes. Market segmentation carried out by PT. Bintang Sidoraya is an offer at a more affordable price and is proven by PT. Bintang Sidoraya succeeded in identifying that they are a company that sells beverage products at affordable prices. This is one of the competitive advantages that can maintain the company's existence in a sustainable manner.